Effects of continuous and rotational cropping practices on soil fungal communities in pineapple cultivation - Chen,Jing; Zeng,Hui (PeerJ, 2022)
Background Rotational cropping practices can change the fungal structure and diversity of cropping soil, and these changes can promote crop development. However, only a few studies have explored the effects of rotational cropping of pineapple on soil fungal diversity. Methods In this study, we investigated fungal diversity in continuous and rotational cropping soil of pineapple in Xuwen and Leizhou of China in summer and winter through high throughput sequencing of the fungal internal transcribed spacer region. Results The diversity and richness of the fungal community were observed to be significantly increased after rotational cropping in Xuwen and Leizhou in summer, whereas no changes were observed in winter. Furthermore, Ascomycota, Basidiomycota, Zygomcota, and Chytridiomycota were the dominant phyla, and Chaetomium, Penicillium, Fusarium, Trichoderma, and Cryptococcus were the dominant genera in the continuous and rotational cropping soil of pineapple, respectively, in both summer and winter. Chytridiomycota at phylum level and Gibberella at genus level were observed in rotational cropping soil; however, Ascomycota at the phylum level and Chaetomium at the genus level were the most abundant fungi, and their abundance dramatically decreased in continuous cropping soil. Redundancy analysis revealed that rotational cropping reduced the correlation between environmental parameters and the fungal community in winter. In addition, several fungal biomarkers were found in Xuwen in both continuous and rotational cropping soil samples, including Sporobolomyces, Aspergillus, Corynascus sp JHG 2007, and Corynascus at the genus level, Penicillium and fungal sp p1s11 at the species level in rotational cropping soil, and ales family Incertae sedis and Sordariomycetes at the class level in continuous cropping soil. These results revealed the changes in the structure and diversity of fungal community in continuous and rotational cropping practices for pineapple cultivation, which may be associated with crop yield and quality.
Keywords: Fungal; Pineapple; Diversity analysis; Soil